Peluang Dan Tantangan Fintech Di Indonesia - Subagja, Gilang; Ihdalumam, Abdy; Vidiati, Cory (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2025)
Fintech (Financial Technology) has experienced a very rapid increase in Indonesia over the past few years and has an important role in the economy. his journal aims to explain the opportunities and challenges of Fintech in Indonesia. This research uses a qualitative descriptive approach method by analysing various references related to the development of fintech in Indonesia. In the results of this journal research explain that the development of  Fintech in Indonesia from year to year continues to increase, Fintech opportunities continue to increase, especially sharia fintech, supported by the majority of the population who are Muslim Kharisma. While the challenge of Fintech is the absence of clear and comprehensive regulations to regulate fintech activities, especially coordination between related institutions such as Bank Indonesia and the Financial Services Authority (FSA).